2015
DOI: 10.1155/2015/571475
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Neural Stem Cell-Based Therapy for Parkinson’s Disease

Abstract: Neural stem cell (NSC) transplantation is an emerging strategy for restoring neuronal function in neurological disorders, such as Parkinson's disease (PD), which is characterized by a profound and selective loss of nigrostriatal dopaminergic (DA) neurons. Adult neurogenesis generates newborn neurons that can be observed at specialized niches where endothelial cells (ECs) play a significant role in regulating the behavior of NSCs, including self-renewal and differentiating into all neural lineage cells. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 86 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…Given that a small pool of neural stem cells are a potential source for replacing degenerated neurons in PD patients [50], we generated NPC lines from a normal or PD patient–derived SNCA-tri iPSC cells and characterized the NPCs with appropriate markers (Fig. 7A–C).…”
Section: Resultsmentioning
confidence: 99%
“…Given that a small pool of neural stem cells are a potential source for replacing degenerated neurons in PD patients [50], we generated NPC lines from a normal or PD patient–derived SNCA-tri iPSC cells and characterized the NPCs with appropriate markers (Fig. 7A–C).…”
Section: Resultsmentioning
confidence: 99%
“…In adults, NSCs are localized in the sub-ventricular zone (SVZ) and hippocampus [21,22]. As with drug therapy, many studies have suggested that NSC transplantation improves cognitive behaviour in animal models of AD [23], Parkinson's disease [24,25] Huntington's disease [26,27], amyotrophic lateral sclerosis [28] and other neurodegenerative diseases. After transplantation, NSCs differentiate into neurons and/or glial cells and release trophic factors.…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…Local factors within the microenvironment of transplanted NSCs affect the fate of the cells, as measured by survival, proliferation, differentiation, and neurogenesis [67]. Several groups have studied modulation of stem cells or DA cells with combined cellular transplantation in animal models of PD ( Table 1) [68]. Besides the attempt to replace damaged tissues, it was shown that grafted cells may promote endogenous vasculogenesis and neurogenesis in the neighboring tissues [69].…”
Section: Restoration Of the Disrupted Neurovascular Microenvironment mentioning
confidence: 99%